2022
DOI: 10.3389/fonc.2022.811084
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Metabolic Syndrome on the Outcome of Hepatitis B-Associated Hepatocellular Carcinoma Patients After Hepatectomy: A Multicenter Study

Abstract: Background and AimsWith changes in dietary patterns and modern lifestyles, the prevalence of metabolic syndrome (MetS) in hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC) patients is increasing. The purpose of our study is to explore the impact of MetS on the prognosis of HBV-associated HCC patients following radical hepatectomy.MethodsData on consecutive HCC patients who underwent radical hepatectomy were prospectively obtained and retrospectively analyzed from seven medical centers in west a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…However, for patients with diagnosed HCC, the influence of MetS on their survival remains unclear (18). Some previous studies showed that MetS may be a risk factor of poor survival of patients with HCC (19)(20)(21)(22)(23), while other studies did not show similar results (24)(25)(26)(27)(28). In this study, we performed a systematic review and metaanalysis to comprehensively investigate the association between MetS and survival of patients with HCC.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…However, for patients with diagnosed HCC, the influence of MetS on their survival remains unclear (18). Some previous studies showed that MetS may be a risk factor of poor survival of patients with HCC (19)(20)(21)(22)(23), while other studies did not show similar results (24)(25)(26)(27)(28). In this study, we performed a systematic review and metaanalysis to comprehensively investigate the association between MetS and survival of patients with HCC.…”
Section: Introductionmentioning
confidence: 89%
“…In addition, 1071 articles were excluded since their titles and abstracts were not relevant to the meta-analysis, leaving 26 studies in total for the full-text review. Finally, after excluding 16 studies through full-text review, ten studies (19)(20)(21)(22)(23)(24)(25)(26)(27)(28) were included. The reasons for the removing of the 16 studies are also presented in Figure 1.…”
Section: Studies Obtainedmentioning
confidence: 99%
See 3 more Smart Citations